2017
DOI: 10.1016/j.tre.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A matheuristic for the Cargo Mix Problem with Block Stowage

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Christensen and Pacino [31] proposed a solution to the problem of cargo bulk blocking. They found that the demand for efficient and cheap transportation and fierce competition have resulted in lower transport rates, forcing carriers to use their vessels in the most efficient way [31]. Lee et al [32] used archival data to research a decision support system for understanding vessel speed in marine logistics, which provides more than 70% of global transport.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Christensen and Pacino [31] proposed a solution to the problem of cargo bulk blocking. They found that the demand for efficient and cheap transportation and fierce competition have resulted in lower transport rates, forcing carriers to use their vessels in the most efficient way [31]. Lee et al [32] used archival data to research a decision support system for understanding vessel speed in marine logistics, which provides more than 70% of global transport.…”
Section: Methodsmentioning
confidence: 99%
“…This work presented a generalization of the slot planning problem that arises when the liner shipping industry needs to plan the placement of containers within a vessel (stowage planning). Christensen and Pacino [31] proposed a solution to the problem of cargo bulk blocking. They found that the demand for efficient and cheap transportation and fierce competition have resulted in lower transport rates, forcing carriers to use their vessels in the most efficient way [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Container loading problems mainly address the issues of planning the loading order and loading position on the basis of ensuring certain constraints [1][2][3]. Study on optimization of container loading problems has an extensive engineering background and various applications on the modern management of container terminals and container shipping [4][5][6]. The container loading problem is a Nondeterministic Polynomial-(NP-) Hard problem that focuses on establishing mathematical models and seeking efficient algorithms depending on the specific environments [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When containers with the same discharge port are clustered together, it is easier for the terminal to implement more advanced handling operations such as dualcycling (interchanging load and discharge operations) and tandem lifts (moving more than one container at the time). The modelling of block stowage is already present in the scientific work of e.g [1] and [4]. To the best of the author's knowledge, no research has been published on the modelling of crane intensity and its combination to a block stowage policy.…”
Section: Introductionmentioning
confidence: 99%